Kinematic modeling and error analysis of Delta robot considering parallelism error. (9th October 2019) - Li, Yu; Shang, Deyong; Liu, Yue
Motion accuracy is an important indicator to evaluate the performance of robots. The driven arm of the Delta robot is composed of a pair of parallelogram mechanisms. Because of the errors in components processing and installation, the parallelogram-driven mechanism will tilt. In addition, the load will have greater inertia impact on the end-effector in high-speed working condition. Therefore, the parallelogram-driven mechanism and loading effect will cause the parallelism error of the moving platform and affect motion accuracy of the robot. Aiming at the error analysis and motion accuracy of the Delta robot, currently, most studies mainly consider the influence of dimension error, clearance error, and driving error. There are few research conducted on the kinematics and error analysis considering parallelism error of the mechanism. The purpose of this article is to study the influence of parallelism error on motion accuracy of the robot. Firstly, the space vector method in mathematics is used to calculate the forward solution of the robot, and the kinematic equations of each kinematic chain are established. Secondly, the article analyzes the influence of the non-parallelism of the driven mechanism on motion error of the robot. Taking the D3PM-1000 robot as an example, it is obtained from the simulation results that with the increase in the tilt angle of the moving platform, the motion error caused by parallelism error also increases and the variation value is obvious, especially in the z direction, meaning that the parallelism error has a great influence on the motion error of the mechanism. The article effectively complements the research field of error analysis and provides a theoretical reference for the error compensation of the robot.